The significance of urgent ultrasound scan for shoulder dislocation in patients above the age of 40: A prospective British Elbow and Shoulder Society pathway implementation study. (June 2021) - Zhou, R; Prasad, G; Robinson, S; Shahane, S; Sinha, A
Background: The highlight of the British Elbow and Shoulder Society pathway for the management of traumatic anterior shoulder instability is early imaging in patients aged over 40 years to assess rotator cuff integrity and early repair, if indicated to optimise function. The senior author set up a protocol in our institute to streamline the diagnostic process for this cohort of patients. This was a retrospective analysis from a prospectively collected database to highlight the importance of early specialist imaging. Methods: Our protocol is to perform urgent ultrasound scans for all suitable patients above 40 years after first-time traumatic shoulder dislocation. Demographics, associated injuries, ultrasound scan results, operations and functional outcomes were collated. Results: One year following the introduction of our protocol, 40 patients with a mean age of 67 (range, 42–89; SD = 13.1) had ultrasound. The incidence of full-thickness rotator cuff tears was 57.5% (n = 23). Eleven patients with confirmed full-thickness rotator cuff tears underwent surgery. The mean age of surgical patients was significantly younger than the non-surgical group (p = 0.004). Discussion: The use of early diagnostic imaging demonstrated a high incidence of full-thickness rotator cuff tears in this cohort of patients. This allowed early surgical repair to optimise function.